(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The main thrust of the Kerala economy is allegedly its consumers. Using environmentally friendly items is crucial to Kerala’s development. It is imperative to shift Kerala’s current level of environmental awareness and emphasize society’s environmental obligations. The three main pollution issues Kerala is currently confronting are air, water, and noise pollution. This study also aims to determine whether Kerala consumers are reluctant to purchase environmentally friendly goods. Both primary and secondary data are extensively used in this study. Then, the primary data was collected through the questionnaire method from the consumers. For this study 75 respondents were selected positively. For collecting necessary data, 75 respondents have been collected in Trivandrum district by using convenience sampling method.